Demokrasi dan kapitalisme global pasca perang dingin - Budiawan Budiawan (Jurnal Civics: Media Kajian Kewarganegaraan)
Democracy do not just measure can take place it general election by prosedural in a state, but core of democracy that is confessing of mirror democracy have to in it. More than that journey and prospect democracy in Indonesia, goodness of level of national and also local there is tendency determined by those who own the capital. Indicator that democracy determined by visible capital owner at legislative institute good process recruitment and also executive. Correct expression to depict the situation "power of capital of bow of power moral". From other side the problem recruitment opening opportunity to be influenced by capital owner also at public policy determination Grow on the problem causing political life domain determined by those who own the capital or incidence of process of subduing of moral power by capital power is because of global capitalism victory after ending of cold war, what is won by capitalism ideology- neoliberalism. Indonesia state as part of existing state in child take care of the international capitalism strength over a barrel to secede from the grasp from international capital strength clutch. Have the power the capital has ended almost entire all political life domain. For overcome this problem, is hence needed by the make-up of society ability for the self-organization and fight for the importance and also its requirement. This society ability represents the last fortress to weaken the danger neo liberalism.